1995
DOI: 10.1111/j.1751-1097.1995.tb09880.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Kinetics and Intracellular Localization of Hypocrellin Photosensitizers for Photodynamic Therapy: A Confocal Microscopy Study

Abstract: Hypocrellins are naturally occurring compounds with photosensitizing properties in biological systems. We have prepared synthetic derivatives of hypocrellin B, which have promise as photosensitizers in the clinical application of photodynamic therapy. The intracellular localization and uptake kinetics of hypocrellin B and several selected hypocrellin congeners were determined semiquantitatively by fluorescence confocal microscopy in monolayer cultures of EMT6/Ed murine tumor cells. Each compound had unique upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 24 publications
5
26
0
1
Order By: Relevance
“…Others have found that photosensitizers localize to a variety of cellular sites including the outer membrane, lysosomes, mitochondria and the nucleus resulting in damage to these structures upon light exposure (Morgan et al, 2000;Oleinick and Evans, 1998). Although mitochondria are primary targets for some photosensitizers, other organelles were also considered as sites of action (Granville and Hunt, 2000;Lee et al, 1995;Miller et al, 1995). The present data provides evidence that internal membranes, particularly, the ER/Golgi apparatus is a distinct site from which an apoptotic signal can emerge.…”
Section: Discussionsupporting
confidence: 49%
“…Others have found that photosensitizers localize to a variety of cellular sites including the outer membrane, lysosomes, mitochondria and the nucleus resulting in damage to these structures upon light exposure (Morgan et al, 2000;Oleinick and Evans, 1998). Although mitochondria are primary targets for some photosensitizers, other organelles were also considered as sites of action (Granville and Hunt, 2000;Lee et al, 1995;Miller et al, 1995). The present data provides evidence that internal membranes, particularly, the ER/Golgi apparatus is a distinct site from which an apoptotic signal can emerge.…”
Section: Discussionsupporting
confidence: 49%
“…18 The cells were viewed directly in 35-mm petri dishes to which a small quantity of mounting medium (50:50, PBS:glycerol) and a coverslip were added. For uniformity, all physical parameters pertaining to fluorescence illumination and detection were held constant as follows: ×63 or ×100 oilimmersion objective lenses; KP 590 short-pass excitation filter; dual dichroic beam-splitter 488/568; BP535 (fluorescein) barrier filter; LP 590 (Texas red) barrier filter; photomultiplier gain, 800 V; pinhole, 60; offset, −45.…”
Section: Clsmmentioning
confidence: 99%
“…The unbound fluorescent antibody was removed by extensive washing in PBS, and the slides were covered with coverslips for confocal microscopy using PBS/glycerol, 1:1 as a mounting medium. The instrumentation and the procedures for the confocal laser scanning microscopy have been described previously (38).…”
Section: Fig 4 Activities Of Recombinant Pnk a Comparison By Sds-mentioning
confidence: 99%